Active Case Finding for Malaria: A 3-Year National Evaluation of Optimal Approaches to Detect Infections and Hotspots Through Reactive Case Detection in the Low-transmission Setting of Eswatini. (16th May 2019) - Hsiang, Michelle S; Ntshalintshali, Nyasatu; Kang Dufour, Mi-Suk; Dlamini, Nomcebo; Nhlabathi, Nomcebo; Vilakati, Sibonakaliso; Malambe, Calsile; Zulu, Zulisile; Maphalala, Gugu; Novotny, Joseph; Murphy, Maxwell; Schwartz, Alanna; et al.
Abstract: Background: Reactive case detection (RACD) is a widely practiced malaria elimination intervention whereby close contacts of index cases receive malaria testing to inform treatment and other interventions. However, the optimal diagnostic and operational approaches for this resource-intensive strategy are not clear. Methods: We conducted a 3-year prospective national evaluation of RACD in Eswatini, a malaria elimination setting. Loop-mediated isothermal amplification (LAMP) was compared to traditional rapid diagnostic testing (RDT) for the improved detection of infections and for hotspots (RACD events yielding ≥1 additional infection). The potential for index case–, RACD-, and individual-level factors to improve efficiencies was also evaluated. Results: Among 377 RACD events, 10 890 participants residing within 500 m of index cases were tested. Compared to RDT, LAMP provided a 3-fold and 2.3-fold higher yield to detect infections (1.7% vs 0.6%) and hotspots (29.7% vs 12.7%), respectively. Hotspot detection improved with ≥80% target population coverage and response times within 7 days. Proximity to the index case was associated with a dose-dependent increased infection risk (up to 4-fold). Individual-, index case–, and other RACD-level factors were considered but the simple approach of restricting RACD to a 200-m radius maximized yield and efficiency. Conclusions: We present the first large-scale national evaluation of optimal RACD approaches from a malaria elimination setting. To inform delivery of antimalarial drugs or other interventions, RACD, when conducted, should utilize more sensitive diagnostics and clear context-specific operational parameters. Future studies of RACD's impact on transmission may still be needed. Abstract : Optimal approaches to find malaria infections and hotspots in reactive case detection are not clear. Here, molecular testing compared to standard rapid diagnostic testing and operational factors (≥80% coverage, response ≤7 days, and 200-m screening radius) maximized efficiency and yield.